Size-dependence of volatile and semi-volatile organic carbon content in phytoplankton cells - Ruiz-Halpern, Sergio; Echeveste, Pedro; Agustí, Susana; Duarte, Carlos M. (Frontiers in Marine Science, 2014)
The content of volatile and semivolatile organic compounds (VOC and SOC), measured as exchangeable dissolved organic carbon (EDOC), was quantified in 9 phytoplanktonic species that spanned 4 orders of magnitude in cell volume, by disrupting the cells and quantifying the gaseous organic carbon released. EDOC content varied 4 orders of magnitude, from 0.0015 to 14.12 pg C cell-1 in the species studied and increased linearly with increasing phytoplankton cell volume following the equation EDOC (pg C cell-1) = -2.35 x cellular volume (CV, µm3 cell-1) 0.90 (± 0.3), with a slope (0.90) not different from 1 indicating a constant increase in volatile carbon as the cell size of phytoplankton increased. The percentage of EDOC relative to total cellular carbon was small but varied 20 fold from 0.28 % to 5.17 %, and no obvious taxonomic pattern in the content of EDOC was appreciable for the species tested. The cell release rate of EDOC is small compared to the amount of carbon in the cell and difficult to capture. Nonetheless, the results point to a potential flux of volatile and semivolatile phytoplankton-derived organic carbon to the atmosphere that has been largely underestimated and deserves further attention in the future.